*•**Let's now look at equations of the form ax² + bx
= 0** *

e.g. x²+2x=0

*•**If you know how to factorise, you'll be fine with this. **We factorise the equation into: *

x
(x + 2) = 0

*•**This could be true when *__x = 0__, since 0 times the bracketed term = 0. However, there remains another *possibility: the bracketed
term itself is 0: *

(x + 2) = 0

*•**We can now ignore the brackets: x + 2 = 0** *

So the solution is: __x = -2__

*•**So, the solutions to x² + 2x = 0 are *__x = 0__ or __-2 __